Brugada Syndrome and Pregnancy: Highlights on Antenatal and Prenatal Management - Laura Giambanco; Domenico Incandela; Antonio Maiorana; Walter Alio; Luigi Alio (Case Reports in Obstetrics and Gynecology)
Introduction. Brugada syndrome is characterized by a disruption of heart’s normal rhythm. It is an autosomal dominant disease due to a mutation of SNC5A gene. Its prevalence is low all over the world, but it is a lethal disease. Sudden cardiac death is the result of phenotypic manifestation of Brugada syndrome. Among asymptomatic Brugada patients, arrhythmia could be provoked by physical activity, fever, or pregnancy. About obstetrical management, very few data or reports have been published since this syndrome has been diagnosed in late 1992. Case Presentation. A 20-year-old pregnant woman at 13 weeks of gestation was referred to our department because of her familial history of sudden cardiac deaths. Brothers and sisters of her mother died of Brugada syndrome in childhood or older and live components of this family were carrier of mutation in Brugada gene. The pregnancy was uneventful. The patient gave birth vaginally without any arrhythmia. Strictly cardiological monitoring was performed during labour, delivery, and 12 hours of the postpartum. Conclusion. Even though patient at low risk may never have arrhythmia, some conditions could represent a Brugada trigger. The management could be very easy and uneventful. Otherwise it could be very difficult with need of ECMO or antiarrhythmics drugs or intracardiac device. Obstetrical management of Brugada pregnant women should be very strict and multidisciplinary in cooperation with cardiologist and anaesthesiologist and should provide an informed consent to the couple.